Respuesta :
Hello there!
5y+8 = 2y-3x+5 solve for y
5y + 8 = 2y - 3x + 5
First, let's subtract 8 from each side
5y + 8 = 2y - 3x + 5
-8 -8
5y = 2y - 3x - 3
Now, let's subtract 2y from each sid
5y = 2y - 3x - 3
-2y -2y
3y = -3x - 3
Now, let's divide each side by 3
3y(/3) = -3x(/3) - 3(/3)
y = -x - 1
I hope I helped!
~ Fire
5y+8 = 2y-3x+5 solve for y
5y + 8 = 2y - 3x + 5
First, let's subtract 8 from each side
5y + 8 = 2y - 3x + 5
-8 -8
5y = 2y - 3x - 3
Now, let's subtract 2y from each sid
5y = 2y - 3x - 3
-2y -2y
3y = -3x - 3
Now, let's divide each side by 3
3y(/3) = -3x(/3) - 3(/3)
y = -x - 1
I hope I helped!
~ Fire